The Analysis of Social Deixis in the Movie Beauty and the Beast - Igaratu Noerrofi’a; Syaiful Bahri (Pioneer: Journal of Language and Literature, 2019)
Social deixis usually can be found in movies. So that, this study purposed to describe the kinds of social deixis and aims of social deixis in the movie entitled Beauty and the Beast. The writers analyzed this study by using theory of Stephen C. Levinson. In analyzing the data of this study, the writers used qualitative method. The findings of the analysis revealed that there were 34 utterances that containing social deixis found in the movie Beauty and the Beast. The writers found 68 styles of social deixis in the movie Beauty and the Beast, 34 styles of social deixis were categorized as kinds of social deixis and 34 styles of social deixis were also categorized as the aims of social deixis. The writers found two kinds of social deixis, they were; 18 styles of social deixis in relational social deixis and 16 styles of social deixis in absolute social deixis. Besides the writers found, three aims of social deixis, they were; 9 styles of social deixis have categorized as to express politeness and respect, 18 styles of social deixis had categorized as to express intimacy, and 7 styles of social deixis had categorized as to identify authority.